Variation in response rates to isolated limb perfusion in different soft-tissue tumour subtypes: an international multi-centre study - Reijers, Sophie; Davies, Emma; Grünhagen, Dirk J.; Fiore, Marco; Honore, Charles; Rastrelli, Marco; Vassos, Nikolaos; Podleska, Lars E.; Niethard, Maya; Jakob, Jens; Perhavec, Andraz; Duarte, Carlos; et al. (European journal of cancer, 2023)
Objective - The aim of this study was to investigate the response rates of different extremity soft-tissue sarcoma subtypes (eSTS) after isolated limb perfusion (ILP), based on an international multi-centre study. - Materials and methods - The retrospective cohort comprised eSTS patients from 17 specialised ILP centres that underwent melphalan-based ILP, with or without recombinant human tumour necrosis factor (rhTNFα) (TM-ILP and M-ILP, respectively). Response was measured on imaging (magnetic resonance imaging) and/or clinical response, for which M-ILPs were excluded. - Results - A total of 1109 eSTS patients were included. The three most common histological subtypes were undifferentiated pleomorphic sarcoma (17%, n = 184), synovial sarcoma (16%, n = 175) and myxofibrosarcoma (8%, n = 87). rhTNFα was used in 93% (TM-ILP) and resulted in a significantly better overall response rate (ORR, p = 0.031) and complete responses (CR, p < 0.001) in comparison to M-ILP, without significant differences among histological subgroups. The ORR of TM-ILP was 68%, including 17% CR. Also, 80% showed progressive disease. Significantly higher response rates were shown for Kaposi sarcoma (KS) with 42% CR and 96% ORR (both p < 0.001), and significantly higher CR rates for angiosarcoma (AS, 45%, p < 0.001) and clear cell sarcoma (CCS, 31%, p = 0.049). ILP was followed by resection ≤ 6 months in 80% of the patients. The overall limb salvage rate was 88%, without significant differences among histological subgroups, but was significantly higher for ILP responders compared to non-responders (93% versus 76%, p < 0.001). - Conclusion - ILP resulted in high response and LRS among all eSTS subtypes, however, with significant differences between subtypes with most promising results for KS, AS and CCS.